The Origin of Non-thermal Fluctuations in Multiphase Flow in Porous Media - Rücker, Maja; Georgiadis, Apostolos; Armstrong, Ryan T.; Ott, Holger; Brussee, Niels; van der Linde, Hilbert; Simon, Ludwig; Enzmann, Frieder; Kersten, Michael; Berg, Steffen (Frontiers in Water, 2021)
Core flooding experiments to determine multiphase flow in properties of rock such as relative permeability can show significant fluctuations in terms of pressure, saturation, and electrical conductivity which is typically not considered in the Darcy scale interpretation but treated as noise. However, in recent years, flow regimes that exhibit spatio-temporal variations in pore scale occupancy related to fluid phase pressure changes have been identified at the pore scale. They are associated with topological changes in the fluid configurations caused by pore-scale instabilities such as snap-off. The common understanding of Darcy-scale flow regimes is that pore-scale phenomena and their signature should have averaged out at the scale of representative elementary volumes (REV) and above. In this work it is demonstrated that pressure fluctuations observed in centimeter-scale experiments commonly considered Darcy-scale at fractional flow conditions where wetting and non-wetting phases are co-injected into porous rock at small (<10-6) capillary numbers are ultimately caused by pore-scale processes but there is also a Darcy-scale fractional flow theory aspect. By comparing fluctuations in fractional flow experiments conducted on samples of few centimeters size with respective experiments with in-situ micro-CT imaging at pore-scale resolution using synchrotron-based X-ray computed micro-tomography we can establish a systematic causality from pore to Darcy scale. At the pore scale dynamic imaging allows to directly observe the associated breakup and coalescence processes of non-wetting phase clusters which follow “trajectories” in a “phase diagram” defined by fractional flow and capillary number and can be used to categorize flow regimes. Connected pathway flow would be represented by a fixed point while processes such as ganglion dynamics follow trajectories but are still overall capillary-dominated. That suggests that the origin of the pressure fluctuations observed in centimeter-sized fractional flow experiments are capillary effects. The energy scale of the pressure fluctuations corresponds to 105-106 times the thermal energy scale. This means the fluctuations are non-thermal. At the centimeter scale, there are non-monotonic and even oscillatory solutions permissible by the fractional flow theory which allow fluctuations to be visible and – depending on exact conditions – significant at centimeter scale, within the viscous limit of fractional flow theory.